Italian Normative Data for the Original Version of the Tower of London Test: A Bivariate Analysis on Speed and Accuracy Scores. (March 2022) - Bruni, Francesca; Toraldo, Alessio; Scarpina, Federica
The Tower of London (ToL) test is traditionally used to assess strategical reasoning, problem-solving, and mental planning in clinical populations. Here, we provide the Italian standardization norms for the original, 12-problem version of the ToL test. The performance of 216 Italian individuals ranging 18 to 89 in age was scored in terms of both Time ( Speed ) and Accuracy —the time, and the number of attempts, necessary to find a solution. We performed univariate analyses on separate Time and Accuracy scores, using Age in years, Education in years, and Sex (male vs. female) as predictors. z scores and equivalent scores were provided. Moreover, we performed a bivariate analysis for the assessment of individuals' performance in terms of Time and Accuracy simultaneously. This standardization allows clinicians to use the original, most widespread version of ToL with the Italian population, thus optimizing comparability with other clinical and experimental research worldwide. Critically, this article offers a new statistical perspective on how Time and Accuracy scores, which are typically related to each other, can be combined to obtain a single, consistent clinical categorization that captures most of the information contained in the patient's performance.